Farm structures: roles and challenges in meeting the needs of the Nigerian farmer (2006)
Although oil is the major source of Nigeria's revenue at present, agriculture is the single largest contributor to the well-being of the rural poor. Agriculture sustains 90% of the rural labour force, provides 60% of industrial raw materials, and contributes 30% to the GDP, with 90% of the output coming from the smallholder farmers. The Nigerian smallholder farmers face a lot of challenges. They are constrained from expanding their farm sizes due to limited labour supply. Poor farm transportation and severe post-harvest losses reduce their economic fortune while the productivity of the farmer and his livestock are reduced by inadequate housing. Farm structures' intervention in the provision of good access roads for farm machinery movement would enable farmers to expand their farm holdings, appropriate crop storage structures which reduce post harvest losses, and cheap but comfortable housing will provide an enabling environment for increased productivity and income. The present Farm Structures curriculum as taught in many institutions needs to be beefed up while farm structures workshops and laboratories should be provided and well equipped. The establishment of a farm structures network is suggested.